2008
DOI: 10.1093/epirev/mxn006
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and Place

Abstract: One important line of epidemiologic inquiry implicating social context in the etiology of psychosis is the examination of spatial variation in the distribution of psychotic illness. The authors conducted a systematic review of evidence from urbanicity and neighborhood studies regarding spatial variation in the incidence of psychosis in developed countries since 1950. A total of 44 studies (20 of urbanicity and 24 of neighborhood) were culled from three databases with similar time frames: Medline (1950-2007), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
194
2
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(231 citation statements)
references
References 92 publications
11
194
2
7
Order By: Relevance
“…This mental disorder was associated with local population density in urban area. 18 One of them was a cohort study on 690,000 Swedish citizens. The study emphasized that born in urban was related with schizophrenia risk for late onset (hazard ratio 1.24).…”
Section: Discussionmentioning
confidence: 99%
“…This mental disorder was associated with local population density in urban area. 18 One of them was a cohort study on 690,000 Swedish citizens. The study emphasized that born in urban was related with schizophrenia risk for late onset (hazard ratio 1.24).…”
Section: Discussionmentioning
confidence: 99%
“…Grup içi ilişkilerin bir göstergesi olan sosyal sermaye, sosyal stres ve dopamin arasında bir tampon işlevi görüyor olabilir (Allardyce ve Boydell 2006, March ve ark. 2008.…”
Section: Bulgularunclassified
“…2008. Düşük sosyal sermayeli bölgelerde yetişen bireylerin edineceği gü-vensizlik atıfları, genetik yatkınlığın psikotik bir atağa dö-nüşmesini kolaylaştırabilir ya da tam tersine, yüksek sosyal sermayeye sahip olan ortamlarda yetişen bireyler genetik yatkınlık taşısalar bile psikotik belirtilerin çekirdek özelliklerini taşıyan yanlış atıflar, o bölgenin özellikleri nedeniyle psikotik düzeye ulaşmayabilir (Allardyce ve Boydell 2006, March ve ark. 2008.…”
Section: Bulgularunclassified
“…1 Of course there is nothing original (to me) in such questions: as my collaborators and I have elaborated elsewhere, questions like these have concerned scholars of all stripes (as well as other writers and investigators) for more than 100 years. 2 They continue to capture scholarly and popular attention today: as I was writing this chapter, Scientific American published an in-depth analysis of two new studies on the association between city living and schizophrenia, 3 Vice carried a story on how placing trees and parks in urban neighbourhoods can have a marked effect on mental health, 4 and The Guardian suggested that Cardiff (my own city) was notable for having an especially high rate of panic attack.…”
mentioning
confidence: 99%